ANALISIS MATERIAL HANDLING PADA PEKERJAAN PEMBUATAN PAVING BLOK DI SURYATAMA BETON - Ismi Mashabai; Iksan Adiasa; Syahrul Ardiansyah (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2021)
The growth and development of the world of science and technology, especially in the industrial sector, is running very fast. It is for this reason that it is necessary to conduct direct research in the industrial world with the target of increasing insight and knowledge about the industrial world, including insight into the material handling process. Thus there is continuity between the knowledge learned in college and its application in the real world of work. Furthermore, it is hoped that students can face the challenges that occur and be able to solve existing problems. Higher education has the responsibility as an institution in shaping young generations with noble character, quality in science and technology, creating strong character, integrity and discipline. Suryatama Beton is a company engaged in the concrete industry which produces products such as paving blocks, concrete buis , pots, well rings and various other products. Therefore, with this research the author tries to analyze whether the company Suryatama Beton can apply the material handling process or not because this process is very good to be applied in the company.